Comparative the efficacy and safety of Gosuranemab, Semorinemab, Tilavonemab, and Zagotenemab in patients with Alzheimer’s disease: a systematic review and network meta-analysis of randomized controlled trials - Cai, Wenting; Zhang, Hui; Wu, Yan; Yao, Yao; Zhang, Jinping (Frontiers in Aging Neuroscience, 2025)
ObjectiveThe aim of this study was to compare the efficacy and safety of anti-tau protein monoclonal antibodies for Alzheimer’s disease (AD). Tau protein aggregation, a key pathological feature of AD, is closely associated with neurodegeneration and cognitive decline. Targeting tau protein has emerged as a promising therapeutic strategy. By investigating the effects of monoclonal antibodies on cognitive function, disease progression, and overall quality of life in patients with AD, which can provide valuable insights into their potential as a therapeutic option for this devastating neurodegenerative disorder.MethodsThe randomized controlled trials (RCTs) investigating the efficacy of Gosuranemab, Semorinemab, Tilavonemab, and Zagotenemab in Alzheimer’s disease (AD) were systematically searched across PubMed, Embase, Web of Science and Cochrane Library, up to May 2024. The control group included placebo. The efficacy indicators were change in the Mini Mental State Examination (MMSE), Clinical Dementia Rating Scale Sum of Boxes (CDR-SB), Alzheimer’s Disease Assessment Scale-Cognitive (ADAS-Cog), Alzheimer’s Disease Cooperative Study-Activities of Daily Living Scale (ADCS-ADL) from baseline until the time of efficacy observation. Statistical analysis was conducted using Stata 14 and RevMan 5.4. The purpose of data processing, including generating network evidence plots, surface under the cumulative ranking curve (SUCRA) ranking, league plots, and funnel plots, is to visually summarize and evaluate the relative effectiveness and safety and potential publication bias of multiple interventions. Mean differences (MD) and 95% confidence interval (95%CI) as effect sizes to analyze continuous variables.ResultsThis study encompassed six RCTs involving 2,193 patients. Semorinemab were more effective than placebo in MMSE and ADAS-Cog scores (MDs ranging between 0.52 and 3.21; MDs ranging between 0.17 and 3.30). Placebo showed relatively good efficacy according to SUCRA ranking on change in CDR-SB and ADCS-ADL scores (75.7 and 79.5%). Tilavonemab and Semorinemab exhibited efficacy similar to that of a placebo in the analysis of the two indicators. Tilavonemab showed a lower incidence of AE, SAE, fall, and urinary tract infections than placebo, and the differences were statistically significant. Most safety analysis results showed no statistical difference.ConclusionThe results indicated that anti-tau protein monoclonal antibodies, such as Semorinemab and Tilavonemab, showed promise in terms of efficacy and safety for managing AD. Further studies are needed to confirm these findings, assess long-term effects, and refine treatment protocols.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, CRD42024583388.